Hispanos en el mundo Emociones y desplazamientos históricos, viajes y migraciones - Gallo González, Danae; Leuzinger, Mirjam; Dolle, Verena (De Gruyter, 2021)
Moving elsewhere is a moving thing. This volume sheds light on the interdependence of emotion and the migration of Hispanics in the world. The essays, written in Spanish and English and departing from various perspectives and disciplines, analyze different media in which Spanish-speaking individuals express their feelings about their travels, their personal experience with migration, and the repercussions of historic migration movements.